A LOOK AT THE HISTORY OF UZBEK FOLK INSTRUMENTS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
In the development of musical art, the importance of musical instruments gathered under the general concept of "music" is incomparable. This article talks about Uzbek folk instruments and the history of its origin.